Blood transfusion and cancer surgery outcomes: A continued reason for concern - Al-Refaie, Waddah B.; Parsons, Helen M.; Markin, Abraham; Abrams, Jerome; Habermann, Elizabeth B. (Surgery, 2012)
The adverse effects of blood transfusion after cancer surgery have been recently challenged in older anemic persons or those with substantial intraoperative blood loss. We hypothesized that intraoperative blood transfusions continue to adversely impact short-term cancer surgery outcomes regardless of age or preoperative hematocrit levels. Using the 2005 to 2008 American College of Surgeons National Surgical Quality Improvement Program, we identified 38,926 patients who underwent cancer surgery. Pre-, intra-, and postoperative factors were compared by units of blood transfusion a patient received. Stratified multivariable analyses, by age and hematocrit level, were performed to assess the impact of blood transfusion on operative outcomes, adjusting for covariates. Fourteen percent of patients received an intraoperative blood transfusion. Of those, >60% received only 1 to 2 units of blood. Receipt of intraoperative blood transfusion was associated with higher rates of 30-day operative mortality, major complications, total number of complications, and prolonged length of stay across age groups and in persons with low to normal hematocrit levels. The present study shows that intraoperative blood transfusion adversely impacts short-term operative cancer surgery outcomes across all age groups and in those with low to normal hematocrit levels. These findings provide insightful implications on the patterns of blood transfusion during cancer surgery that deserve further investigation.